Determination of uranium in tree bark samples by epithermal neutron activation analysis (Brazilian Journal of Radiation Sciences, 2019)
In this study uranium (U) concentrations were determined in certified reference materials (CRMs) and in tree bark samples collected in “Cidade Universitária Armando de Salles Oliveira” (CUASO) USP, São Paulo. The barks were collected from different species namely Poincianella pluviosa and Tipuana tipu. These bark samples were cleaned, dried, grated and milled for the analyses by epithermal neutron activation analysis method (ENAA). This method consists on irradiating samples and U standard in IEA-R1 nuclear reactor with thermal neutron flux of 1.9 x 1012 n cm-2 s-1 during 40 to 60 seconds depending on the samples’ matrices. The samples and standard were measured by gamma ray spectroscopy. U  was identified by the peak of  74.66 keV of 239U with half life of 23.47 minutes. Concentration of U was calculated by comparative method. For analytical quality control of U results, certified reference materials were analyzed. Results obtained for CRMs presented good precision and accuracy, with |Z score| ≤ 0.39. Uranium concentrations in tree barks varied from 83.1 to 627.6 ng g-1 and the relative standard deviations of these results ranged from 1.8 to 10 %.